ASSESSMENT OF STRESS IN CALF USING VOCALIZATION MEASUREMENT - SILVA, RAFAEL AUGUSTO DA; TOLON, YAMILIA BARRIOS; NÄÄS, IRENILZA DE ALENCAR; MOURA, DANIELLA JORGE DE; SOUZA, SILVIA REGINA LUCAS DE (Revista Brasileira de Engenharia de Biossistemas, 2007)
Calf management in commercial milk production requires the separation of the calf from the cowa short time after delivery. This management raises two opinions: one is that it allows higherprotection to the young animal; and the other is that this procedure is harmful limiting its movementand resulting in low welfare condition. This research had the objective of estimating stress conditionin female calves reared in individual boxes by measuring their vocalization. Five female calveswere used divided into two groups related to their age: two were older and three were younger.The vocalization emitted by the animals was recorded and processed. The frequency and noiselow and high pith spectrum were studied. It was not found difference between the quantity of peaknoise and the female calves' age group. The results showed that in all studied animal resultingspectra it was observed a decrease in the amplitude with the increase of the frequencies, wherethe highest amplitudes were of low pitch which is an indication of stress. It was also found that thelength of time of the young calves was longer indicating a state of fear. It was concluded thatyoung calves present higher stress when separated from the cow